Mastering the digital innovation challenge - Svahn, Fredrik; Mathiassen, Lars; Lindgren, Rikard; Kane, Gerald C. (MIT Sloan Management Review, 2017)
For Volvo Cars, pursuing digital innovation required fundamentally rethinking the organization, while also keeping the core business functioning efficiently. The company did so by balancing four interrelated competing concerns: (1) new and established innovation capabilities; (2) process and product focus; (3) external and internal collaboration; and (4) flexibility and control in relationships with external partners.
"Reprint #58315.". - Includes bibliographical references. - Description based on online resource; title from cover (Safari, viewed April 24, 2017)
Keywords: Volvo Car Corporation; Automobile industry and trade -- Technological innovations; Automobiles -- Electronic equipment; Automobiles; Industrie et commerce; Innovations; Automobiles; Équipement électronique; Automobile industry and trade; Technological innovations; Automobiles; Electronic equipment